Does Functionality Cease after Acquired Brain Injury? Vignettes from a Neuropsychosocial Perspective - Chopra, Sakshi; Sinha, Sumit; Gupta, Deepak; Satyarthee, Guru Dutta; Agrawal, Deepak; Kaloiya, Gaurishanker; Sagar, Rajesh; Tripathi, Manjari; Nehra, Ashima (Indian Journal of Neurotrauma, 2017)
Background The outcome of acquired brain injury (ABI) depends largely on the nature and severity of injury, appropriate treatment, and rehabilitation that plays a vital role in recovery.Materials and Methods A total of 18 patients after ABI, aged 18 to 50 years, were assessed pre- and post-neuropsychological rehabilitation (NR) on various psychosocial functions. The patient-specific NR included an eclectic approach using cognitive retraining for memory, attention and concentration, executive functioning, perceptuomotor speed, motor dexterity, basic functional skill training, cognitive behavior therapy, rational emotive behavior therapy, relearning, relaxation therapy, assertiveness training, anger management, and vocational and individual counseling following a neuropsychosocial perspective.Results The post-rehabilitation assessment revealed improvements of statistical and clinical significance in the score of on dysfunction analysis (t = 7.10) that was significant at 0.001 level. Significant improvements were found in each of the areas: social, vocational, personal, family, and cognitive as compared with pre-rehabilitation as described by the patient.Discussion and Conclusion Eclectic approach to NR was successful in decreasing the overall dysfunction of the patients despite the severity of injury or the time elapsed after injury. Several therapeutic approaches have been used to assist individuals after brain injury, but more outcome studies are still needed to dictate which therapy works best, or if using an eclectic therapy is the key. The challenge is to make the therapy as person centered and individualistic as possible, depending on the individual needs as there is no “gold standard” for treatment for various issues arising following brain injury.
Keywords: cognition; brain injury; rehabilitation; India